State Policy Regulations of Agriculture for Sustainable Development of Rural Tourism - AIMURZINA, Baglan; YERTARGYN, Shakhman; NURMAGANBETOVA, Aigul; NARYNBAYEVA, Aina; ABDRAMANOVA, Gulzhan; MIZAMBEKOVA, Zhamilya (Journal of Environmental Management and Tourism, 2023)
In order to ensure the high efficiency of the functioning of the actors of the rural tourism sector, it is necessary to conduct a comprehensive study, taking into account its sustainable development. This research paper underlines that the particular features of state regulation of the domestic agro-industrial complex need the expansion of state support tools through the development of rural tourism, conducting in same time at diversification factors helping its development. The paper explores state policy regulations underling the positive effects of rural tourism upon economy as a whole, factors that influences development of tourism, the integration of agriculture activities with those of tourism which implies constant inter-sectoral interaction; last but not least is analyzed the data on the share of agriculture and rural tourism in the structure of Kazakhstan's GDP, the level of the average monthly nominal wage of one employee by type of economic activity which is unappealing due the fact the structure peasants’ farms could be a mean rural tourism in which economy is enhanced.